Beta-Blockade in Intraseptal Anomalous Coronary Artery With Reversible Myocardial Ischemia. Issue 1 (January 2021) - Doan, Tam T.; Qureshi, Athar M.; Sachdeva, Shagun; Noel, Cory V.; Reaves-O'Neal, Dana; Molossi, Silvana
Anomalous aortic origin of a left coronary artery (L-AAOCA) with an intraseptal course is a rare anomaly and can be associated with myocardial ischemia and sudden cardiac death. No surgical or medical intervention is known to improve patient outcomes. A 7-year-old boy with intraseptal L-AAOCA presented with nonexertional chest pain, syncope, and had reversible myocardial ischemia on provocative testing. The patient was started on β-blockade, following which his symptoms improved and resolved over a period of six years. A follow-up dobutamine stress magnetic resonance imaging no longer showed reversible ischemia, and cardiac catheterization with fractional flow reserve did not show coronary flow compromise.